Edukasi Mengenai GUT Microbiota dan Peran Probiotik terhadap Kesehatan Saluran Cerna pada Anak Gizi Kurang - Komalasari, Husnita; Prima Arzani, Lalu Danu; Heldiyanti, Rina; Adinda Putri, Destiana; Nizhar Naufali, Muhammad; Hidayah, Nurul (Insan Kreasi Media, 2022)
East Lombok is one of the districts in the province of West Nusa Tenggara which still has a high number of children with undernutrition. Undernutrition is a condition in which the body does not get adequate nutritional intake for growth, development and maintaining health. The purpose of this community service activity is to provide knowledge to the community and students about the gut microbiota and the role of probiotics on gastrointestinal health in malnourished children. The method of this activity is counseling and filling out questionnaires before and after counseling. Based on the results of the questionnaire, it was found that there was an increase in the knowledge of the counseling participants, namely 100% of the participants knew the benefits of balanced nutrition in children; the definition of stunting, undernutrition and malnutrition; the effect of good nutrition on development and growth; undernutrition causes children to experience developmental disorders, reduced levels of intelligence and academic achievement; and probiotics and the role of probiotics for gastrointestinal health. However, only 47% of participants were able to answer foods that were included in the 4 healthy 5 perfect foods. So we conclude that the target of this community service activity already understands the socialization material presented.